Toward (car)borane‑based molecular magnets - Oliva, Josep M. (2015)
In a previous work, we reported the electronic structure of dimer diradicals composed of two S = ½ closo-carborane CB11H· 12 structural units (Theor. Chem. Acc. (2013) 132: 1329). That work has been extended here in order to describe a linear dimer, a linear and a cyclical trimer, and a tetrahedral structure of these units connected by means of a –CH2– bridge. A mapping of the resulting spin states onto a Heisenberg spin Hamiltonian is proposed for these new chains providing the evaluation of spinexchange coupling constants.